A Numerical Study of Mixed Convection in Square Lid-Driven with Internal Elliptic Body and Constant Flux Heat Source on the Bottom Wall (Journal of Scientific Research, 2017)
The mixed convection in square lid-driven with internal elliptic body and constant flux heat source on the bottom wall is numerically simulated in this paper following a finite element method approach. The left moving wall and right moving wall are cold. The upper wall is insulated and so is the lower wall with heat flux located in the middle. The magnetic field of strength B is applied parallel to x- axis. Result is presented for different Richardson numbers (0.01 ? Ri ? 10) when Grashof numbers are (10 ? Gr ? 50) and Prandtl number is taken as Pr = 0.733 for all computations. The influence of the Richardson number on heat source surface is being investigated in this paper. Results are presented in the form of streamline and isotherm plots as well as the variation of the maximum temperature and Nusselt number at the heat source surface under different conditions. A detailed analysis of flow pattern shows that the mixed convection is based on the parameters Richardson number (Ri), Grashof number (Gr) and Reynolds number (Re).